Fully-Depleted SOI MOSFET Sensors in Accumulation Mode for Total Dose Measurement - Alcalde Bessia, F. (2018)
Fil: Alcalde Bessia, F. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina